Highly strained Ge micro-blocks bonded on Si platform for mid-infrared photonic applications. (10th July 2017) - Gassenq, A.; Guilloy, K.; Pauc, N.; Rouchon, D.; Widiez, J.; Rothman, J.; Hartmann, J.-M.; Chelnokov, A.; Reboud, V.; Calvo, V.
Abstract: Abstract : Applying sufficient tensile strain to Ge leads to a direct bandgap group IV semiconductor, which emits in the mid-infrared (MIR) wavelength range. However, highly strained-Ge cannot be directly grown on Si because of its large lattice mismatch. In this work, we have developed a process based on Ge micro-bridge strain redistribution intentionally landed to the Si substrate. Traction arms were then partially etched to keep locally strained-Ge micro-blocks. Large tunable uniaxial stresses up to 4.2% strain were demonstrated in Ge, which was bonded on Si. Our approach allows envisioning integrated strained-Ge on Si platform for MIR-integrated optics. Silicon photonics merge optical and electronic components that can be integrated together onto a single microchip.